The Impact of ROE, DER, & EPS on Stock Prices in Non-Bank LQ-45 Indeks Company - Yulitsya Cahya Praptiningtiyas Tiyas; Annisa Annisa (CAKRAWALA : Management Science Journal, 2026)
The purpose of this study is to examine and empirically prove the influence of Return on Equity (ROE), Debt to Equity Ratio (DER), and Earnings Per Share (EPS) on stock prices. The population consists of non-bank companies listed in the LQ-45 Index on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. A total of 35 companies were selected using a purposive sampling technique. The data were analyzed using a panel data regression model with the Fixed Effect Model (FEM) approach through EViews version 13 software. The results indicate that ROE has a significant positive effect on stock prices, while DER has a significant negative effect. Meanwhile, EPS was found to have no significant effect on stock prices, suggesting that earnings per share information has already been reflected in market prices. Simultaneously, the independent variables explain 95.34% of the variation in stock prices. These findings imply that investors should prioritize the analysis of profitability and capital structure over earnings per share when making investment decisions in LQ-45 stocks.